Difficulties in social cognitive functioning among pediatric patients with muscular dystrophies - García, Irune; Martínez, Oscar; López-Paz, Juan Francisco; García, Maitane; Rodríguez, Alicia Aurora; Amayra, Imanol (Frontiers in Psychology, 2024)
Pediatric muscular dystrophies (MDs) are a heterogeneous group of rare neuromuscular diseases characterized by progressive muscle degeneration. A neuropsychosocial approach is crucial for these patients due to associated cognitive, behavioral, and psychiatric comorbidities; however, the social cognitive domain has not been adequately addressed. This study aimed to analyze on social cognition performance in a pediatric MD patient cohort. This cross-sectional study included 32 pediatric patients with MD and 32 matched-healthy controls. The Social Perception Domain of the NEPSY-II, the Reading the Mind in the Eyes Test-Child and Happé's Strange Stories Test were administered. General intelligence and behavioral and emotional symptoms were controlled for to eliminate covariables' possible influence. The assessments were performed remotely.Children with MDs performed significantly worse on most of the social cognition tasks. The differences found between the groups could be explained by the level of general intelligence for some aspects more related to theory of mind (ToM) (TM NEPSY-II: F = 1.703, p = .197; Verbal task: F = 2.411, p = .125; RMET-C: F = 2.899, p = .094), but not for emotion recognition. Furthermore, these differences were also independent of behavioral and emotional symptoms. In conclusion, social cognition is apparently impaired in pediatric patients with MD, both for emotion recognition and ToM. Screening assessment in social cognition should be considered to promote early interventions aimed at improving these patient's quality of life.